Evaluación de la operación de la planta de tratamiento de aguas residuales del municipio de Ubaté (2015)
The studies and designs of the WWTP of the municipality of Ubaté begin in the year of 1988. In 1991 the construction is completed and its implementation takes place in an agreement between the University of Los Andes and the Regional Autonomous Corporation of Cundinamarca - CAR. At present, there is evidence of low removal in the treatment, which is why in order to establish technical criteria to identify possible shortcomings, the design, operation, efficiencies and operating costs are evaluated.